Sociodemographic, Infectious Diseases, Food Security, and Environmental Conditions in the Family of Children with and without Intraindividual Double Burden Malnutrition WaSt - Purwanti, Rachma; Ajeng, Novitasari Dwi (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Intraindividual double-burden malnutrition, Wasted-Stunted (WaSt), frequently occurs in the same child simultaneously or at different moments throughout their life. This study aims to identify differences in the sociodemographic characteristics, incidence of infectious diseases, food security, and environmental conditions in the family of children with and without WaSt. The research employed a cross-sectional design conducted from April to October 2022 in Semarang City involving 133 subjects. The independent variables included toddler, mother, father, and family characteristics. The dependent variable was WaSt. The statistical tests used were the Kruskal-Wallis test with the Mann-Whitney U test for data that were not normally distributed and the one-way ANOVA test with the Bonferroni post hoc test for normally distributed data. This research shows that 19% of toddlers have WaSt. There were differences in the incidence of infectious diseases, home sanitation hygiene, father’s education, and food security between toddlers with normal nutritional status and the other two groups (stunted and WaSt) with a p-value <0.05. There were no differences in the incidence and types of infection between WaSt and stunted groups. Most family expenditures were allocated to food (70% in the WaSt and stunting groups and 60% in the normal nutritional status group). The government and related stakeholders need to pay more attention to families of children under five with limited access and facilities for hygiene and sanitation, low income, low parental education, and low food security to prevent an increase in the risk of WaSt.